Post-mortem toxicology in young sudden cardiac death victims: a nationwide cohort study. Issue 4 (27th February 2017) - Bjune, Thea; Risgaard, Bjarke; Kruckow, Line; Glinge, Charlotte; Ingemann-Hansen, Ole; Leth, Peter Mygind; Linnet, Kristian; Banner, Jytte; Winkel, Bo Gregers; Tfelt-Hansen, Jacob
Abstract: Aims: Several drugs increase the risk of ventricular fibrillation and sudden cardiac death (SCD). We aimed to investigate in detail the toxicological findings of all young SCD throughout Denmark. Methods and results: Deaths in persons aged 1–49 years were included over a 10-year period. Death certificates and autopsy reports were retrieved and read to identify cases of sudden death and establish cause of death. All medico-legal autopsied SCD were included and toxicological reports collected. Positive toxicology was defined as the presence of any substance (licit and/or illicit). All toxicological findings had previously been evaluated not to have caused the death (i.e. lethal concentrations were excluded). We identified 620 medico-legal autopsied cases of SCD, of which 77% ( n  = 477) were toxicologically investigated post-mortem, and 57% ( n  = 270) had a positive toxicology profile. Sudden cardiac death with positive toxicology had higher rates of sudden arrhythmic death syndrome (SADS), compared with SCD with negative toxicology (56% vs. 42%, P  < 0.01). In total, 752 agents were detected, and polypharmacy (defined as the presence of more than one drug) was present in 61% ( n  = 164), all substances combined. Psychotropic drugs were the most frequent (62%, n  = 467), and 82% ( n  = 385) were in pharmacological or subpharmacological levels. Conclusion: We found that more than half of all toxicologically investigated SCD victims have positive post-mortem toxicological findings, and polypharmacy is displayed in a considerable proportion. SCD with positive toxicology had higher rate of SADS, suggesting that the compounds may play a proarrhythmic role in these cases.